Institute of representation of the people’s power in the history of Belarusian statehood - Krupeichenko, Maxim A. (Journal of the Belarusian State University. Law, 2024)
The author of the article examines the formation, development and features of the institute of representative power of the people in the history of the Belarusian statehood. The origin, role of the veche, its powers as a representative body are studied, and the further formation of veche traditions is analysed. The significance of soims and soimiks as bodies of class representation of the gentry is assessed, their formation and difference from European class-representative bodies are considered. The legal basis for the activities of representative bodies is also covered, and attention is paid to the process of reforming the soimiks’ order.